Influência da quimioterapia com 5-Fluorouracil na osseointegração de implantes instalados em tíbias de ratos: avaliação biomecânica, microtomográfica, histomorfométrica, histoquímica e imunoistoquímica - Ferro-Alves, Márcio Luiz [UNESP] (2016)
The purpose of the present study was to evaluate the influence of chemotherapy treatment with 5- fluorouracil(5-FU) during the initial process of osseointegration, and influence of chemotherapy treatment with 5-FU on osseous tissue maturation phase, on osseointegrated implants, installed at the rat tibia, through biomechanics, microtomography, histomorphometry, histochemistry and immunohistochemistry evaluation, through the detection of immunomarkers tartrate-resistant acid phosphatase (TRAP), osteocalcina (OCN). Sixty animals were submitted to a surgical procedure to install a titanium implant on their right and left tibia. The animals were randomly separated on the following experimental groups: Group C15/30D (control; n=10) – The animals received the first physiological saline (PS) 15 days after the implants installation; Group C15/45D (control; n=10) – The animals received the first OS 15 days after the implants installation and were euthanized 45 days after the implants installation; Group 5FU15/30D (n=10) – The animals received the first 5-FU chemotherapic shot 15 days after the implants installation and were euthanized 30 days after the implants installation. Group 5FU15/45D (n=10) – The animals received the first shot of 5-FU chemotherapic 15 days after the implants installation and were euthanized 45 days after the implants installation. Group C30/45D (control; n=10) received the first OS shot 30 days after the implants were installed and were euthanized 45 days after the implants installation. Group 5FU30/45D (n=10) – the animals received the first 5-FU chemoterapic shot 30 days after the installation of the implants and were euthanized 45 days after the implants installation. Both left and right tibias were collected and fixed in buffered formalin 4% and 70% ethanol respectively. The pieces were processed to do the biomechanical, microtomography, histomorphometry, histochemistry and immunohistochemistry evaluation. At the biomechanics and histomorphometry analyses the group 5FU15/30D got results below the 5FU15/45D(p<0.05) and 5FU30/45D(p<0.05) groups, as in the analyses microtomography the group 5FU15/30D presented less osseous volume when compared to the 5FU15/45D(p<0.05) group, and the C15/30D group presented less osseous volume when compared to C30/45D(p<0.05) group. The histochemistry analyses of the 5FU15/30D group presented less quantity of mature collagen fibers when compared to C15/30D(p<0.05) e 5FU15/45D(p<0.05) groups. At the immunohistochemistry evaluation of the TRAP marker wasn’t found any differences between the groups, but the OCN marker on 5FU15/30 group presented a low standard of immunostaining when compared to the other groups. It concludes that when the chemotherapy with 5-FU is accomplished during osseointegration it has no negative influence on peri-implant tissues.